Auricular Acupuncture on Uterine Point on PGF2α Levels and First-Stage of Labor Duration among Primigravida Women - Setiawandari Setiawandari; Noor Pramono; Koosnadi Saputra (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2022)
Duration of labor is influenced by four factors, including the power or uterus contraction. Labor contractions begin with a decrease in the progesterone hormone levels and an increase in the oxytocin hormone levels which is initiated by prostaglandins (PGF2α). Auricular acupuncture on uterine point is located in the triangular fossa which is innervated by the trigeminal nerve and the vagus nerve. Stimulation on the uterine point can send a wave of stimulation to the central nervous system in the posterior hypothalamus to produce oxytocin. This study aims to analyze the effectiveness of auricular acupuncture on uterine point on PGF2α levels and the duration of the first stage of labor among primigravida women. This was a true experimental study with a two-group pretest-posttest design. The total sample of the study was 48 women in labor who were selected through a randomized control trial and met the inclusion criteria of low-risk pregnancy. Data were analyzed using the Wilcoxon and Mann Whitney tests. The results of the study revealed that auricular acupuncture on uterine point significantly increased PGF2α levels (ρ=0.002), (201.29±132.916) compared to the deep-breath relaxation group 132.08±93.530. Auricular acupuncture on uterine point was proven to shorten the duration of the first stage of labor (440.3 ± 72.94; 440.00) when compared to the deep breathing relaxation group (517.6 ± 101.00; 507.50) with a very significant difference (ρ=0.004). In conclusion, auricular acupuncture on uterine point was effective in shortening the duration of labor by increasing PGF2α levels.